Modeling anthropic factors as drivers of wildfire occurrence at the Monarch Butterfly Biosphere - Farfán Gutiérrez, Michelle; Pérez-Salicrup, Diego R.; Flamenco-Sandoval, Alejandro; Nicasio-Arzeta, Segio; Mas, Jean-François; Ramírez Ramírez, Isabel (Instituto de Ecología, A.C., 2018)
Fire regimes in coniferous forests in Central Mexico have been severely disturbed by land use change and fire management activities. Hence, it is critical to assess the contribution of anthropic and environmental factors that drive the occurrence of fires in these forests. This information is essential for the effective planning of fire management and wildfire prevention policies. In this study, we identified the potential drivers of fire occurrence within the Monarch Butterfly Biosphere Reserve (MBBR) and modeled their spatial pattern through generalized linear mixed models. We employed fire event data for five years (2009-2013) and the spatial distribution of anthropic infrastructure and biophysical variables such as forest biomass and slope. We found fire occurrence increased with total population and forest edge density. The derived spatial model showed an acceptable accuracy (AUC = 0.71) for fire occurrence based on 2014 and 2015 fire events used to evaluate the model. To improve the model, we suggest the incorporation of direct fuel measurements. From our analyses, we suggest to develop fire management guidelines particularly in sites with high population density and close to forest fragments within the MBBR.